2018
DOI: 10.5897/ajps2017.1547
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical analyses and comparative in vitro antioxidant studies of aqueous, methanol and ethanol stem bark extracts of Simarouba glauca DC. (Paradise tree)

Abstract: This study was conducted to evaluate selected phytochemicals (antioxidant potentials of aqueous, methanol and ethanol stem bark extracts of Simarouba glauca) relative to standard antioxidants. Sample was harvested, air dried, pulverized and extracted with aqueous and absolute methanol and ethanol; freeze dried at the National Energy Commission Centre, University of Benin. Alkaloids, phenols and tannins were identified, a n d also flavonoid was detected. 2,2-Diphenyl-1-picrylhydrazyl (DPPH) radical scavenging a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…Anticancer activity of the leaf extract has been shown in the bladder cell lines [40]. A recent study has reported the phytochemical constituents and the antioxidant activity in the root bark [41]. There are no reports on the comparative study of phytochemicals and antioxidant activity of flowers with respect to leaves and bark.…”
Section: No Radical Scavenging Assaymentioning
confidence: 99%
“…Anticancer activity of the leaf extract has been shown in the bladder cell lines [40]. A recent study has reported the phytochemical constituents and the antioxidant activity in the root bark [41]. There are no reports on the comparative study of phytochemicals and antioxidant activity of flowers with respect to leaves and bark.…”
Section: No Radical Scavenging Assaymentioning
confidence: 99%
“…Fe [II]-TPTZ has an intense blue colour which was taken at 593 nm. Newly prepared FRAP solution (1.5 mL), containing 25 mL of 300 mM acetate buffer at pH 3.6, 2.5 mL of 10 mm 2,3,6-TPTZ in 40 mM HCl, and 2.5 ml of 20 mM Iron(lll)chloride hexahydrate (FeCl 3 .6H 2 O) solution was transferred to 1 mL of the extracts and absorbance taken at 593 nm [14]. Calibration plot was linear between 50 -300 μM and it was prepared with FeSO 4 .7H 2 O solution.…”
Section: Total Antioxidant Assay (Frap Assay)mentioning
confidence: 99%
“…Among them, flavonoids have been shown to exhibit their actions through effects on membrane permeability and by inhibition of membrane-bound enzymes such as the ATPase and phospholipase A2 and this property may explain the mechanisms of antioxidative action of S. glauca. Flavonoids are testified to possess anti-inflammatory, antioxidant, antiproliferative, antitumor, and pro-apoptotic activities; molecular targets have been identified [29]. The health promoting paraphernalia of flavonoids may relate to interactions with key enzymes, signaling cascades involving cytokines and transcription factors, or antioxidant systems.…”
Section: Discussionmentioning
confidence: 99%